Dental caries survey of first permanent molar teeth among 6-8 years old during the pandemic: cross-sectional study - Fadilah, Rina Putri Noer; Prayogo, Ari Pribadi (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: A survey is necessary for annual screening and recording. Dental caries is one of the indicators in oral health surveys. Dental caries is the most common and prevalent chronic infectious disease among children. The most prevalent dental caries is in the child's first permanent molar. The first permanent tooth eruption in the oral cavity was the  first molar of 6-year-old children. This study aims to determine dental caries in first permanent molars among children aged 6-8 years old during the pandemic in Cimahi City, West Java, Indonesia. Methods: The research method used was a cross sectional study with pathfinder surveys using basic oral health survey methods. Schoolchildren were invited to participate in this survey. The survey collected data through intraoral photos and questionnaires through an online form. The prevalence of dental caries was the percentage. After calculation, the data is presented in tables and graphs. Results: The result of this study on 98 children showed that the prevalence of dental caries was 96.93%. The caries index primary teeth (DMFT) mean was 7.86, and the caries index permanent teeth (DMFT) mean was 0.37. Dental caries of the first permanent molar teeth was at 19%. Conclusions: There is a high prevalence of dental caries in primary teeth and high categories of dental caries in primary teeth. The incidence of dental caries in the first permanent molars was 19%.KEY WORDS: dental caries, first permanent molar, childrenSurvei karies gigi pada gigi molar permanen pertama pada anak usia 6-8 tahun selama pandemi : studi cross sectional ABSTRAK Pendahuluan: Survei diperlukan untuk penjaringan dan pencatatan yang digunakan setiap tahun. Salah satu indikator dalam survei kesehatan gigi dan mulut adalah karies gigi. Karies gigi adalah penyakit infeksi kronis yang paling umum dan umum terjadi pada anak-anak. Karies gigi yang paling banyak terjadi adalah gigi molar pertama permanen. Erupsi gigi permanen pertama di rongga mulut adalah gigi geraham pertama yang berumur 6 tahun. Penelitian ini bertujuan untuk mengetahui karies gigi pada gigi geraham pertama permanen pada anak usia 6-8 tahun pada masa pandemi di Kota Cimahi, Jawa Barat, Indonesia. Metode: Metode penelitian yang digunakan adalah cross sectional study dengan menggunakan pathfinder survey dengan metode dasar survey kesehatan gigi dan mulut. Kami mengundang anak-anak sekolah untuk berpartisipasi dalam survei ini. Survey dilakukan dengan mengumpulkan data melalui foto intra oral dan kuesioner dengan menggunakan sistem online yaitu google form. Prevalensi karies gigi dalam bentuk persentase dan disajikan dalam bentuk tabel dan grafik. Hasil: Sebanyak 98 anak menunjukkan prevalensi karies gigi sebesar 96,93%. Rerata indeks karies gigi sulung (dmft) adalah 7,86 dan rerata indeks karies gigi permanen (DMFT) adalah 0,37. Karies gigi gigi molar pertama permanen adalah 19%. Simpulan: Prevalensi karies gigi tinggi pada gigi sulung dan kategori karies gigi tinggi pada gigi sulung. Insiden karies gigi pada gigi molar pertama permanen adalah 19%.KATA KUNCI: karies gigi, gigi molar satu permanen, anak-anak